A dietary strategy for the management of artemether-lumefantrine-induced cardiovascular and renal toxicity. Issue 1 (December 2016) - Asiedu-Gyekye, Isaac; Seidu, Mahmood; N'guessan, Banga; Frimpong–Manso, Samuel; Sarkodie, Joseph; Adjei, Samuel; Kutu, Schevadnazy; Osei-Little, Joseph; Nyarko, Alexander; Debrah, Philip
Abstract Background Unsweetened natural cocoa has antimalarial properties. Unsweetened natural cocoa powder (UNCP), obtained as a result of the removal of cocoa butter from a cocoa bean protects against malaria episodes. Cocoa powder, which is prepared after removal of the cocoa butter, contains about 1.9 % theobromine and 0.21 % caffeine. Concomitant consumption of cocoa and artemether/lumefantrine (A/L) is a common practice in Ghana, West Africa. This study seeks to determine the elemental composition of UNCP and its protective effect on the heart and kidney against (A/L) administration. Methods Energy dispersive x-ray fluorescence spectroscopy was used to detect the quality and quantity of the elemental composition in UNCP. Thereafter, 30 nonmalarious male guinea pigs were divided into five groups of six animals each. One group was administered with 75 mg/kg body weight A/L only and another group distilled water (control group). The rest received 300 mg/kg, 900 mg/kg and 1500 mg/kg body weight UNCP for 14 days orally and A/L for the last 3 days (ie day 11 to day 14). Biochemical and histopathological examinations were carried out after euthanisation of the animals. Results A total of thirty-eight (38) micro and macro elements were detected with the ED-XRF. Macro elements like sodium (Na), magnesium (Mg), aluminium (Al), phosphorus (P), chlorine (Cl), potassium (K), calcium (Ca), manganese (Mn) and iron (Fe) and micro elements like chromium (Cr), copper (Cu), zinc (Zn), arsenic (As), and lead (Pb) were identified and evaluated. Biochemical analysis revealed increases in HDL levels (p >0.05) while there were decreases in LDL levels (p >0.05), creatine kinase and AST levels (P <0.05) in animals that received UNCP compared to A/L only administered group. Urea levels reduced significantly by 53 % (p <0.05) in group that received 1500 mg/kg UNCP. Histopathological examinations of the heart and kidney buttressed the protective effects of cocoa administration. Conclusion The percentage of recommended daily allowance of UNCP for chromium is 3750 % for men and 5250 % for women while % RDA for copper corresponds to 103.6 % in both sexes. UNCP proved to possess cardioprotective and renoprotective potential during artemether-lumefantrine administration.